Implementasi Budaya Kerja Kementerian Agama dalam Proses Pencatatan Nikah - Jamian, Jemian (Fakultas Syariah, 2018)
Public service is one of the country's obligations to the community. The state is obliged to guarantee the rights and fulfill the needs of the community, as mandated by the 1945 Constitution. The services in question can be in the form of goods, services, and / or administrative services. This article aims to describe the implementation of marriage records in the Office of District Religious Affairs based on the work culture spirit of the Ministry of Religion of the Republic of Indonesia. This research is empirical research with a qualitative approach. The research focus is the Office of Religious Affairs in the Blangkejeren District, Gayo Regency. The results of this study indicate that community satisfaction in public services in the field of marriage can be achieved if done by a professional, clean, and accountable apparatus. One effort that can be done is by utilizing the SIMKAH Online application. The use of the SIMKAH Online application in the process of marriage registration in the Office of Religious Affairs is a manifestation of the work culture of professionalism and innovation within the Ministry of Religion.Pelayanan publik merupakan salah satu kewajiban negara kepada masyarakat. Negara wajib menjamin hak dan memenuhi kebutuhan masyarakat, sebagaimana amanat Undang-Undang Dasar 1945.Pelayanan yang dimaksud dapat berupa penyediaan barang, penyediaan jasa, dan/atau pelayanan administratif.Artikel ini bertujuan mendeksripsikan implementasi pencatatan perkawinan di Kantor Urusan Agama Kecamatan berdasarkan semangat budaya kerja Kementerian Agama Republik Indonesia. Penelitian ini termasuk dalam penelitian empiris dengan pendekatan kualitatif. Lokus penelitian adalah Kantor Urusan Agama Kecamatan Blangkejeren Kabupaten Gayo. Hasil penelitian ini menunjukkan bahwa kepuasan masyarakat dalam layanan publik di bidang pernikahan bisa tercapai apabila dilakukan oleh aparatur yang profesional, bersih, dan akuntabel. Salah satu upaya yang bisa dilakukan adalah dengan memanfaatkan aplikasi SIMKAH Online.Penggunaan aplikasi SIMKAH Online dalam proses pencatatan perkawinan di Kantor Urusan Agama merupakan manifestasi dari budaya kerja profesionalitas dan inovasi di lingkungan Kementerian Agama. w:LsdException Lo